MEDICATION PRACTICES AND IMPACT ON GLYCAEMIC OUTCOMES AMONG FASTING MUSLIM TYPE 2 DIABETES MELLITUS IN PRIMARY CARE CLINICS DURING RAMADAN - Theng, Chong Yee (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Ramadan fasting has been shown to affect glycaemic outcomes among those with Type 2 Diabetes Mellitus (T2DM) due to adjustment of oral antidiabetic medications (OHA) and insulin. METHODOLOGY This study investigates how medication practices affect glycated haemoglobin (HbA1c) levels, hypoglycaemia, hyperglycaemia and hospitalization rates among fasting Muslim T2DM patients in Petaling district, Malaysia. A prospective observational study was conducted in seven government primary healthcare clinics in the Petaling district from March 14 to July 15, 2022. A questionnaire on medication types, practices and outcomes was administered to patients. Pregnant women were excluded. Chi-square and logistic regression were used to determine the association between medication practices and glycaemic outcomes. RESULTS A total of 260 participants completed the study. In this study, 96.5% of participants were taking OHA; 41.5% were taking both insulin and OHA. Despite being counseled by healthcare providers (HCPs), 8.4% of participants had self-adjusted their OHAs, and 23.1% self-modified their insulin dose during Ramadan. Among those who adjusted OHAs, 2.2% stopped taking the medication, 6.9% decreased the dose and none increased the dose. For insulin users, 2.6% increased the dose, 9.1% reduced the dose and none discontinued the insulin. Chi-square showed a significant effect of self-adjustment of medication during Ramadan with hypoglycaemia (P = 0.046), with no significant association between self-adjustment of medication with HbA1c level (P = 0.48), hospitalization rate (P = 0.693), or hyperglycaemia (P = 0.757). However, logistic regression did not show any significant association between selfadjustment of medication and hypoglycaemia (P = 0.085). CONCLUSION HCPs need to be aware and do close follow-ups among T2DM patients to prevent self-adjustment of medications during Ramadan. Self-adjustment of medication during Ramadan has no significant impact on glycaemic outcomes. Further studies are needed to explore other factors like medication adherence and dietary and lifestyle changes that may affect such outcomes.